Academic Supervision and Work Climate to Improve Primary School Teacher Performance - Fauziah Yolviansyah; Hermanto; Maftuhatu Rosyidah, Dyana (Jurnal Pendidikan Indonesia, 2024)
The inconsistent implementation of academic supervision reduces the effectiveness of providing support and guidance to teachers, and an unconducive work climate results in a decline in teacher performance. This study aims to analyze the effect of academic supervision and work climate on the performance of elementary school teachers in Bantul District and to evaluate the contribution of academic supervision and work climate partially to the performance of elementary school teachers in Bantul District. This type of research is quantitative research. The population of this study was all elementary schools. The study sample was 136 teachers, using a random sampling technique. The data collection technique used a questionnaire. The data analysis techniques used in this study were multiple regression and partial hypothesis testing (t-test), simultaneous test (f-test), and coefficient of the determinant test (R2). The study's results showed that: partially, academic supervision affects teacher performance with t count, and significantly, partially, work climate affects the performance of elementary school teachers with t count. Simultaneously, there is a positive and significant influence between academic supervision and work climate on teacher performance. This study strengthens previous findings about the importance of academic supervision and work climate in improving teacher performance. The results can guide schools and the government in designing strategies to improve the quality of education at the elementary level. The implications of this study indicate that adequate academic supervision and a conducive work climate play a significant role in improving teacher performance, both in terms of planning, implementing, and evaluating learning.